The Effects of Digital Literacy, Investment Knowledge, Herding Behavior, and Loss Aversion Bias on Digital Investment Decisions - Alfin Rusda Fatwa (Generate Digital Publishing, 2026)
Objective: The digital transformation in the financial sector (fintech) is changing the way people invest, as technology enables faster and more efficient investing through digital platforms that are accessible at any time. This study aims to analyze the influence of digital literacy, investment knowledge, herding behavior, and loss aversion bias on digital investment decisions among the population in Central Java.Research Design & Methods: This study employs a quantitative approach using primary data collected through a questionnaire administered to 347 respondents selected via non-purposive sampling. Data analysis was conducted using multiple linear regression with the aid of SPSS, accompanied by data quality checks and tests of classical assumptions.Findings: The results of the study indicate that digital literacy, investment knowledge, herding behavior, and loss aversion bias have a positive and significant influence on digital investment decisions, both individually and collectively. These findings suggest that investment decisions are influenced not only by cognitive abilities and knowledge but also by social factors and investors’ psychological biases.Implications: In practical terms, the findings of this study underscore the importance of improving digital literacy and investment education to support the quality of the public’s investment decisions. Furthermore, an understanding of behavioral factors such as herding and loss aversion is necessary so that investors can make more rational and informed decisions.Contribution & Value Added: This study contributes to the development of the literature on behavioral finance and financial technology by integrating cognitive, social, and psychological factors within the context of digital investing at the regional level. It also provides an empirical overview of digital investor behavior in Central Java, serving as a foundation for future research and policy-making.